Islam and ecology a bestowed trust - Foltz, Richard C.,d1961-; Denny, Frederick Mathewson; Azizan Haji Baharuddin (Religions of the world and ecology, 2003)
The environmental crisis falls hardest upon the world's poor, a disproportionate number of whom are Muslims. Islam contains a strong message of social justice, which challenges many of the environmentally destructive development models currently in place. Moreover, the Islamic tradition contains rich sources for environmental ethics, although this dimension has not yet figured prominently in the discourse of contemporary Muslim intellectuals who tend to see environmental issues as symptoms of broader social justice concerns." "The conference on Islam and ecology held at the Center for the Study of World Religions, Harvard Divinity School, in 1998 was the first international forum to bring Islamic environmental values to the forefront of discussion. In the Islamic worldview humans are seen as stewards over a creation that belongs ultimately not to humans, but to God